Analysis of eye and head coordination in a visual peripheral recognition task - Simon Schwab; Othmar Würmle; Andreas Altorfer (Journal of Eye Movement Research)
Coordinated eye and head movements simultaneously occur to scan the visual world for relevant targets. However, measuring both eye and head movements in experiments allowing natural head movements may be challenging. This paper provides an approach to study eye-head coordination: First, we demonstrate the capabilities and limits of the eye-head tracking system used, and compare it to other technologies. Second, a behavioral task is introduced to invoke eye-head coordination. Third, a method is introduced to reconstruct signal loss in video-based oculography caused by cornea reflection artifacts in order to extend the tracking range. Finally, parameters of eye-head coordination are identified using EHCA (eye-head co-ordination analyzer), a MATLAB software which was developed to analyze eye-head shifts. To demonstrate the capabilities of the approach, a study with 11 healthy subjects was performed to investigate motion behavior. The approach presented here is discussed as an instrument to explore eye-head coordination, which may lead to further insights into attentional and motor symptoms of certain neurological or psychiatric diseases, e.g., schizophrenia.